Respond OJK Regulation Number 55: Can Good Corporate Governance Affect Banks Credit Risk in Indonesia? - Siswantoro Siswantoro (Politeknik Negeri Jember, 2021)
Efforts to reduce the number of non-performing loans continue to be carried out, one of which is by enforcing the rules regarding good corporate governance as enshrined in POJK Number 55/POJK.03/2016. The purpose of this study is to respond to these regulations by testing whether the attributes of good corporate governance can influence bank credit risk. The total population is 44 established banking companies with three years from 2017 to 2019. The data analysis technique uses descriptive statistical analysis and partial hypothesis testing. The results showed that the size of the Board of Directors and the size of the Risk Monitoring Committee harmed credit risk. Meanwhile, the size of the Board of Commissioners, the proportion of Independent Commissioners, the meeting of the Board of Commissioners, and the size of the Audit Committee does not significantly influence bank credit risk.